Network Pharmacology of Plumbagin for the Treatment of Psoriasis - Purwoko, Mitayani; Mundijo, Trisnawati; Astri, Yesi; Rohani, Siti (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: Psoriasis skin disease brings attention to pharmacology studies; many traditional medicines from plants are defined as promising candidates for this disease treatment. Plumbagin is one candidate that has been proven for several decades for these issues. Methods: The potency of Plumbagin as an anti-psoriasis treatment was analyzed using WAY2DRUG PASS Prediction. Target proteins prediction was analyzed using Pass Protein Target, DIGEP-Pred, and Comparative Toxicogenomic Database. Targets related to Psoriasis were obtained from The Human Gene Database Genecards, Open Target, and PharmGKB. The JVENN tol was used to visualize the Venn Diagram. Protein-protein interaction was analyzed using STRING DB V.12 and the filtered by Cytoscape V.10.1. Functional annotation was analyzed using DAVID. Results: Plumbagin can target proteins interacting with Psoriasis-related proteins such as TP53, CASP3, MAPK3, TNF, AKT1, STAT3, MAPK8, NFKB1, ESR1, and EP300. Conclusions: Plumbagin has good potential as an anti-psoriasis agent.